Green synthesis of propylene oxide directly from propane - Pierre Kube; Jinhu Dong; Nuria Sánchez Bastardo; Holger Ruland; Robert Schlögl; Johannes T. Margraf; Karsten Reuter; Annette Trunschke (Nature Communications, 2022)
Propylene and propylene oxide are formed over boron nitride or SiO2 in the gas phase without yielding large amounts of CO2. Conversion at non-specific interfaces can thus be a successful strategy for the synthesis of oxidation-sensitive products.